2014
DOI: 10.1103/physrevc.89.041601
|View full text |Cite
|
Sign up to set email alerts
|

Dipole excitations via isoscalar probes: The splitting of the pygmy dipole resonance in124Sn

Abstract: Inelastic α-scattering excitation cross sections are calculated for electric dipole excitations in 124 Sn based on the transition densities obtained from the relativistic quasiparticle time-blocking approximation (RQTBA) in the framework of a semiclassical model. The calculation provides the missing link to directly compare the results from the microscopic RQTBA calculations to recent experimental data measured via the (α, α ′ γ) reaction, which show a structural splitting of the lowlying E1 strength often den… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 39 publications
3
35
0
Order By: Relevance
“…Furthermore, experiments with complementary probes like α-particles at intermediate energy, indicate an isospin splitting of the low-lying 1 − states [21]. Similar to the experimental findings, theoretical models show that at lower energies the E1 strength is predominantly of isoscalar character which gradually becomes more isovector with increasing excitation energy toward the IVGDR [18,19,[22][23][24][25][26].…”
Section: Introductionsupporting
confidence: 67%
“…Furthermore, experiments with complementary probes like α-particles at intermediate energy, indicate an isospin splitting of the low-lying 1 − states [21]. Similar to the experimental findings, theoretical models show that at lower energies the E1 strength is predominantly of isoscalar character which gradually becomes more isovector with increasing excitation energy toward the IVGDR [18,19,[22][23][24][25][26].…”
Section: Introductionsupporting
confidence: 67%
“…In the lowenergy region below the neutron threshold of mediummass even-even nuclei this term is responsible solely for the appearing strength. In the relativistic framework, the latter was confirmed and extensively studied [49,61], and verified by comparison to experimental data [50,51,[62][63][64]. However, a comparison with high-resolution experiments on the dipole strength below the neutron threshold has revealed that, although the total strength and some gross features of the strength are reproduced well, the fine features are sensitive to truncation of the configuration space by 2q⊗phonon configurations and further extensions of the method are needed.…”
Section: Relativistic Quasiparticle Time Blocking Approximation: mentioning
confidence: 92%
“…First we note that a skin oscillation would respond strongly in both channels, IS and IV. This is in analogy to the strong IS response expected of neutron-skin modes [33][34][35]. In Fig.…”
Section: Resultsmentioning
confidence: 89%